2018
DOI: 10.1111/sjop.12502
|View full text |Cite
|
Sign up to set email alerts
|

Facilitators and barriers to the implementation of motivational interviewing for bullying perpetration in school settings

Abstract: Bullying is a perplexing and persistent problem with negative consequences for all involved. Schools are assigned considerable responsibility for the management of bullying because of its prevalence amongst youth. Despite considerable efforts over decades to curtail bullying through the use of anti‐bullying policies and other school‐based interventions, the rates of young people who frequently bully has not decreased significantly. Motivational Interviewing (MI) is a relational and affirming conversational met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 54 publications
(60 reference statements)
0
8
0
Order By: Relevance
“…Moral disengagement mechanisms provide fertile cognitive grounds for resistance talk, as they provide internal justifications for why the behavior in this case bullying -was warranted (e.g., moral justification) or even deserved (e.g., victim blame), or alternately, why those behaviors are not acknowledged as being the responsibility of the young person (diffusion of responsibility). However, implementing motivational interviewing can be challenging in schools (Pennell, Campbell, Tangen, Runions, Brooks, & Cross, 2018) given limits to the capacity to deliver selective interventions.…”
Section: Discussionmentioning
confidence: 99%
“…Moral disengagement mechanisms provide fertile cognitive grounds for resistance talk, as they provide internal justifications for why the behavior in this case bullying -was warranted (e.g., moral justification) or even deserved (e.g., victim blame), or alternately, why those behaviors are not acknowledged as being the responsibility of the young person (diffusion of responsibility). However, implementing motivational interviewing can be challenging in schools (Pennell, Campbell, Tangen, Runions, Brooks, & Cross, 2018) given limits to the capacity to deliver selective interventions.…”
Section: Discussionmentioning
confidence: 99%
“…We tested the use of Motivational Interviewing with entrenched bullying behaviours to support students to identify and act upon their own motivations for engaging in bullying . Our research identified important barriers to implementation of this approach, as well as implementation enablers (Pennell et al, 2020) that will support future trials of innovative responses to bullying. This research, however, suggests it is promising for school counsellors to support bullying perpetrator behaviour change .…”
Section: Treatmentmentioning
confidence: 95%
“…Findings from these studies and consumers informed the adaption of these resources to respond to specific higher bullying risk contexts, including cyberbullying (Cross et al, 2015); critical periods of change, such as the transition from primary school to secondary school (Cross, Shaw et al, 2018); and more specialised support for students frequently involved in bullying behaviour (e.g., Pennell et al, 2020) and who require more culturally or contextually co-designed interventions, such as Aboriginal and Torres Strait Islander students (Coffin et al, 2010), and students who face chronic physical health conditions, such as deafness or hard of hearing (Kishida et al, 2021).…”
Section: Friendly Schools' Researchmentioning
confidence: 99%
“…Qualitative studies have helped to 'unmask' these complexities and identify factors that appear to enable or inhibit the effective implementation of school-based bullying prevention interventions through a deeper look at the influencing contextual factors and processes (Pennell et al, 2020;Coyle, 2008;O'Donoghue & Guerin, 2017;Young et al, 2017;Locke et al, 2019). Guiding frameworks such as the Consolidated Framework for Implementation Research (Damschroder et al, 2009) and the Framework for Implementation Quality in Schoolbased Interventions (Domitrovich et al, 2008) have also helped to define potential barriers to quality implementation at individual, organisational and wider-system levels.…”
Section: Introductionmentioning
confidence: 99%